Pengaruh Pendekatan Matematika Realistik terhadap Minat Belajar Mahasiswa Tadris/Pendidikan Matematika pada Saat Pandemi Covid-19 - Lili Nur Indah Sari (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2021)
The purpose of this study was to see the effect of the Realistic Mathematics Approach on student interest in learning during the covid-19 pandemic. This research is a quasi-experimental research (quasi-experimental) conducted at the Padangsidimpuan State Islamic Institute, Faculty of Tarbiyah and Teacher Training, Tadris/Mathematics Education Study Program T.A 2019/2020. The conclusion from the questionnaire results obtained from students, the average score of student interest in learning who was treated with the Realistic Mathematics Approach was better than the average score of student interest in learning who was treated with the Conventional Approach. The average score of students who were treated with a realistic mathematical approach was 50.03, while the average score of students who were treated with the Conventional Approach was 41.73. In the calculation of the t test, the t value was obtained at a significance level of 0.151 0.05 so it can be concluded that there is an effect of a realistic mathematical approach on the learning interest of Tadris/Mathematics Education students during the covid-19 pandemic.